Reading Michael Palin's Himalaya from an Insider's Perspective - Upadhyay, Toya Nath (Humanities and Social Sciences Journal, 2022)
This study reads Michael Palin's travel text, Himalaya (2004) from a cultural insider's perspective and argues how the author gets trapped into the vestiges of conventional Western outlook upon the non-West. Surfacely and even intentionally, the author appears to keep himself away from such outlook, but it resurfaces frequently in the text and exemplifies how the traditional colonial tendency of stressing superiority keeps lurking in the Western travel writers' texts. The author makes a trip across seven nations in 2003 but as a resident of Nepal I focus my analysis on his travel in Nepal. For the analytic purpose, the study borrows conceptual insights from scholars in travel writing genre such as Carl Thompson, Robert Clarke and Debbie Lisle. Terms related to colonial discourse theory will be heavily used.